Improvement of energy resolution of ΔE-E CsI/SSD telescope at measurement of (γ,p)-reactions using strip information of SSD - Brudvik, G.; Burdeinyi, D.D.; Ganenko, V.B.; Hansen, K.; Fissum, K.; Isaksson, L.; Livingston, K.; Lundin, M.; Nilsson, B.; Schröder, B. (Вопросы атомной науки и техники, 2016)
Information on the triggered strips of silicon strip detectors of a MAX-lab ΔE-E CsI/SSD-telescope was used to determination the angular range of emitted reaction particles. It allowed an improvement in the energy resolution of the telescope by decreasing the kinematical broadening of the missing energy spectra of ¹²C(γ,p)¹¹B reaction, and enabling more accurate separation of exited states of residual nucleus.